KEPALA SEKOLAH SEBAGAI PEMIMPIN PENDIDIKAN MENGENAI KESENJANGAN DAN PENYIMPANGAN DI SDN NO 50/VI LUBUK MENTILIN - Sukmawati; Subhanadri (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Abstract This research aims to find out the principal as an educational leader regarding gaps and deviations at SDN 50/VI Lubuk Mantilin Kec. Anchor. This research includes evaluative research using the Descrepancy Model. Measuring the effectiveness of the program is carried out by comparing two things at the end of the program, namely the beginning and end of program implementation, namely comparing ideal conditions with real conditions regarding school principal standards. Variables are measured with instruments in the form of questionnaires. The results show that there are two main problems, namely gaps and deviations in the elementary school environment in Lubuk Mantilin Village.. The resuits of the first research are as follows, firstly, the gap includes several things a) leaderships quality gap, b) resource gap, c) treatment gap, d) implementations gap, e) communication gap. And as for the second result, the following are several devications that may accur, a) administrative deviatus, b) ethial deviations, c) devications in curriculum implementation, d) principal deviations in assesment. The results of the two studies show that there are action to overcome and reprimand the accurrenre of gaps and deviations at SDN 50/VI Lubuk Mentilin based on 8 national educatonal standards, namely content standards, process standards, graduate competency standards, standards for educators and education staff. Keywords : school principal, educational leader, disparities and iregularities